2021
DOI: 10.1302/0301-620x.103b3.bjj-2020-0800.r1
|View full text |Cite
|
Sign up to set email alerts
|

Kingella kingae septic arthritis

Abstract: Aims The aim of this study was to determine the extent to which patient demographics, clinical presentation, and blood parameters vary in Kingella kingae septic arthritis when compared with those of other organisms, and whether this difference needs to be considered when assessing children in whom a diagnosis of septic arthritis is suspected. Methods A prospective case series was undertaken at a single UK paediatric institution between October 2012 and November 2018 of all patients referred with suspected sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…22 The ESR/CRP ratio appears as a promising tool in patients with OAI caused by K. kingae. 34 In our study, the median ESR/CRP ratio was higher in group 2 and reached statistical significance in distinguishing K. kingae from the rest of pathogens. When comparing patients with SA, OM, OM-SA from group 1 and 2, those whose causative agent was K. kingae versus the rest of the patients (including those with sterile culture), we identified that an ESR/CRP ratio <0.67 made it possible to rule out, with 91% sensitivity, the presence of K. kingae.…”
Section: Discussionsupporting
confidence: 56%
“…22 The ESR/CRP ratio appears as a promising tool in patients with OAI caused by K. kingae. 34 In our study, the median ESR/CRP ratio was higher in group 2 and reached statistical significance in distinguishing K. kingae from the rest of pathogens. When comparing patients with SA, OM, OM-SA from group 1 and 2, those whose causative agent was K. kingae versus the rest of the patients (including those with sterile culture), we identified that an ESR/CRP ratio <0.67 made it possible to rule out, with 91% sensitivity, the presence of K. kingae.…”
Section: Discussionsupporting
confidence: 56%
“…However, culture-negative septic arthritis has been reported in up to two-thirds of the cases [28]. K. kingae has been reported to be the most commonly isolated organism from PCR-positive confirmed septic arthritis [29]. Routine cultures performed at most facilities could detect only one-third of these cases.…”
Section: Table 4: Variations In Late Presenting Septic Arthritis Of T...mentioning
confidence: 99%
“…It reported that the bacterium was detected in 76% of children younger than 48 months with arthritis and 53% of those with osteomyelitis. 21 The leading role of K. kingae as a skeletal system pathogen of early childhood has been demonstrated in Western countries such as the USA 30,31 ; Canada 32 ; Western European countries (Portugal, 33 Spain, 34 France, [19][20][21]25 the UK, 35 and Switzerland 18,22,23,[36][37][38] ); Australia 39 and Israel. 40 These observations do not imply that K. kingae infections are restricted to the industrialised world.…”
mentioning
confidence: 99%